2023
DOI: 10.1186/s13072-022-00476-1
|View full text |Cite
|
Sign up to set email alerts
|

ATAC-seq and RNA-seq analysis unravel the mechanism of sex differentiation and infertility in sex reversal chicken

Abstract: Background Sex determination and differentiation are complex and delicate processes. In female chickens, the process of sex differentiation is sensitive and prone to be affected by the administration of aromatase inhibitors, which result in chicken sex reversal and infertility. However, the molecular mechanisms underlying sex differentiation and infertility in chicken sex reversal remain unclear. Therefore, we established a sex-reversed chicken flock by injecting an aromatase inhibitor, fadrozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…An in-depth investigation has confirmed that the variation in chromatin accessibility corresponds to the alteration of gene expression [163]. For instance, compared to females, the transcriptional activity of DMRT1 in males is upregulated, which is accompanied by increased chromatin accessibility [163]. Based on these findings, we conclude that epigenetic regulation plays a key role in controlling the activation and maintenance of masculine developmental pathways in birds.…”
Section: Genetic and Epigenetic Regulation In Male Sex Differentiationmentioning
confidence: 51%
See 3 more Smart Citations
“…An in-depth investigation has confirmed that the variation in chromatin accessibility corresponds to the alteration of gene expression [163]. For instance, compared to females, the transcriptional activity of DMRT1 in males is upregulated, which is accompanied by increased chromatin accessibility [163]. Based on these findings, we conclude that epigenetic regulation plays a key role in controlling the activation and maintenance of masculine developmental pathways in birds.…”
Section: Genetic and Epigenetic Regulation In Male Sex Differentiationmentioning
confidence: 51%
“…Notably, epigenetic factors are likely to contribute to maintaining gonadal fate. The chromatin accessibility of DMRT1 in embryonic female-to-male sex-reversed chickens cannot be increased to the normal male level, corresponding to its transcriptional activity [163]. In addition, the pattern of DNA methylation around CYP19A1 in estrogen-mediated sex-reversed chicken gonads fails to be induced to form the same as that in control females, suggesting that epigenetic elements are involved in the establishment of avian gonadal CASI [177,178].…”
Section: Avian Sex Reversal and Cell Autonomous Sex Identitymentioning
confidence: 95%
See 2 more Smart Citations
“…Combining this technique with RNA-seq greatly enhances our understanding of gene regulation. Researches using both omics technologies to investigate mechanisms such as sex differentiation ( Li et al, 2022b ; Zhang et al, 2023a ) and the fate specification of feathers/scales ( Lai et al, 2018 ) has been conducted, while studies on muscle development during the embryonic period remain scarce.…”
Section: Introductionmentioning
confidence: 99%